Recalibrating International Investment Arbitration: The Green Constitution as an Ecological Justice Defense - Sheilla Bintang Aerielisty (Siyasah Dusturiyah: State Law Review, 2026)
Contemporary international investment law faces a structural legitimacy crisis due to the normative clash between foreign direct investment protection and global ecological sustainability imperatives. This research urgently addresses the regulatory chill phenomenon resulting from arbitration mechanisms that weaponize treaty protections against state climate mitigation policies. Employing doctrinal legal research, this study rigorously analyzes treaties, customary international law, and arbitral jurisprudence utilizing the Vienna Convention on the Law of Treaties. The findings demonstrate that domestic supreme law, conceptualized as the Green Constitution, serves as a proactive doctrinal defense. By establishing an implied incorporation clause, the Green Constitution redefines investors' legitimate expectations ab initio and fortifies state police powers. The research concludes that systemically integrating ecological constitutionalism into arbitration, mandated by Article 31(3)(c), recalibrates international economic law, effectively mitigating corporate lawfare and subordinating commercial expectations to the erga omnes obligations of global environmental justice within the modern foreign direct investment legal framework.